Extended-range, low coherence dual wavelength interferometry using a superfluorescent fibre source and chirped fibre bragg gratings - Kalli, Kyriacos; Webb, David J.; Jackson, David A. (My University, 1997)
We describe an all-fibre, passive scheme for making extended range interferometric measurements based on the dual wavelength technique. The coherence tuned interferometer network is illuminated with a single superfluorescent fibre source at 1.55 μm and the two wavelengths are synthesised at the output by means of chirped fibre Bragg gratings. We demonstrate an unambiguous sensing range of 270 μm, with a dynamic range of 2.7 × 105
Keywords: Optical fibers; Diffraction gratings; Interferometers